Review of the four item Morisky Medication Adherence Scale (MMAS-4) and eight item Morisky Medication Adherence Scale (MMAS-8) - Xi Tan; Isha Patel; Jongwha Chang (University of Minnesota Libraries Publishing, 2014)
Erratum Redacted by authors in order to address a question regarding the use of a measure.    Type: Original Research